2013
DOI: 10.1111/1745-7599.12031
|View full text |Cite
|
Sign up to set email alerts
|

Level of acculturation, food intake, dietary changes, and health status of first-generation Filipino Americans in Southern California

Abstract: This study underscores the importance of nurse practitioners and other healthcare givers conducting cultural dietary assessment as a basis for culturally appropriate dietary counseling. The inclusion of waist measurement to regularly monitor abdominal obesity-a predictor of cardiovascular disease and diabetes-is highly recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Interestingly, despite the high rate of chronic conditions in the sample, many respondents rated their health as good or excellent. This is not dissimilar to the findings of Dela Cruz et al [ 22 ] who found that Filipinos have good self-rated health despite higher than normal anthropometric measures, an indication of increased risk for chronic diseases. Becker [ 23 ] reported that a cultural characteristic of Filipino Americans is minimising the impact or presence of illness which could help explain this finding.…”
Section: Discussionsupporting
confidence: 64%
“…Interestingly, despite the high rate of chronic conditions in the sample, many respondents rated their health as good or excellent. This is not dissimilar to the findings of Dela Cruz et al [ 22 ] who found that Filipinos have good self-rated health despite higher than normal anthropometric measures, an indication of increased risk for chronic diseases. Becker [ 23 ] reported that a cultural characteristic of Filipino Americans is minimising the impact or presence of illness which could help explain this finding.…”
Section: Discussionsupporting
confidence: 64%
“…Despite representing one of the largest populations in the United States, the health of Filipino Americans and other Asian American subgroups is poorly understood and not well studied [2,4]. Public health studies have either examined Asian American subgroups individually, generalizing these findings to all Asian Americans, or have aggregated Asian Americans into one group, which may misrepresent the differences in disease prevalence among different subgroups [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This population also has higher smoking rates and binge drinking rates compared with other Asian American subgroups [8]. As Filipino Americans are a highly acculturated ethnic group, they may exhibit bicultural eating patterns than reflect both a preference for food that is typically American and traditionally Filipino [4]. More specifically, the Western dietary acculturation scale, which measures Western eating patterns that include a high intake of fat and sugar, was a significant predictor of the increase in anthropometric factors such as body mass index (BMI) and weight in Filipino Americans [14].…”
Section: Introductionmentioning
confidence: 99%
“…Upon arrival, these new U.S. immigrants undergo acculturation—the “process by which an immigrant adopts the language, customs, behaviors, and attitudes of the host culture” (Lee, O'Neill, Ihara, & Chae, , p. 2). Acculturation has been shown to influence dietary practices (dela Cruz, Lao, & Heinlein, ; Serafica, Lane, & Ceria‐Ulep, ); medication adherence, lifestyle behaviors, and blood pressure control (Tailakh et al., ); and obesity and cardiovascular risk factors (Shah et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Since its development and original validation, the studies using ASASFA involved first-generation (Philippine-born) Filipinos (dela Cruz & Galang, 2008;dela Cruz et al, 2013;Ea, 2007;Kataoka-Yahiro, 2010;McAdam, Stotts, Padilla, & Puntillo, 2005;Reyes & Cohen, 2013;Serafica et al, 2013). Very little research on its use with U.S.-born FAs exists.…”
mentioning
confidence: 99%